My Own Private Germany : Daniel Paul Schreber's Secret History of Modernity - Santner, Eric L. (Book collections on Project MUSE., 2001)
In November 1893, Daniel Paul Schreber, recently named presiding judge of the Saxon Supreme Court, was on the verge of a psychotic breakdown and entered a Leipzig psychiatric clinic. He would spend the rest of the nineteenth century in mental institutions. Once released, he published his Memoirs of My Nervous Illness (1903), a harrowing account of real and delusional persecution, political intrigue, and states of sexual ecstasy as God's private concubine. Freud's famous case study of Schreber elevated the Memoirs into the most important psychiatric textbook of paranoia. In light of Eric Santne.